CD Review: C Force Deep Blue - Walters, Adam (International Journal of Bahamian Studies, 2014)
The Caribbean is well known for the indigenous musical forms that evolved during the region’s colorful and frequently troubled history. Mass migration resulting from the slave trade threw together the musical traditions of Africa, Europe and North America resulting in styles such as junkanoo (The Bahamas), reggae (Jamaica) and soca (Trinidad) to name just a few that have grown to become widely popular today. Far less known, however, is the small yet significant repertoire of “art music” written by composers living and working in the region.